Impact of COVID-19 pandemic on acute stroke care in a tertiary stroke centre - Máté Héja; István Fekete; Sándor Márton; László Horváth; Klára Fekete (Scientific Reports)
Abstract The aim of this study was to evaluate how COVID-19 affected acute stroke care and outcome in patients with acute ischemic or hemorrhagic stroke. We performed a retrospective analysis on patients who were admitted with acute ischemic (AIS) or hemorrhagic (ICH) stroke from September 2020 to May 2021 with and without COVID-19. We recorded demographic and clinical data, imaging parameters, functional outcome and mortality at one year. Beside descriptive statistics we performed χ2-probe, Mann-Witney U-test, Student t-probe and multivariate testing. We found a 29%-reduction in the number of AIS cases during the pandemic. The number of the large vessel occlusions /LVOs/ (N = 83, 41.7%), from them 37 (17.7%) had mechanical thrombectomy (MT), was higher than before the COVID-19 period (p = 0.02 and p = 0.001, respectively). From all patients needing acute revascularization therapy (N = 137) 118 patients received it, among them 20 (16.9%) had COVID-19. Those positive for COVID-19 were more likely to have a higher median NIHSS score at baseline and at 24 h (p = 0.02 and p = 0.03, respectively). They also had a lower rate of favourable outcome at discharge (15% vs. 41.8%; p = 0.024) and at three months (25% vs. 52%, p = 0.02), longer median hospitalization (p < 0.0001), and a higher mortality rate (52% vs. 25%; p = 0.03). The incidence of symptomatic intracerebral hemorrhage (sICH) did not differ between the groups. Regarding the ICH patients, NIHSS score at 24 h (p = 0.036), mortality at 3 months (p = 0.004) and at one year (p = 0.00) were higher in the COVID-19 group. We concluded that the pandemic resulted fewer admission due to AIS with an increased number of LVOs and MTs. AIS patients with concomitant SARS-CoV-2 infection have more severe strokes and unfavorable long term outcome. The risk of sICH was not increased in COVID-19 positive patients therefore reperfusion therapies appear to be safe and beneficial for some individuals. Patients with ICH and comorbid COVID-19 have a very poor prognosis.